2023
DOI: 10.1126/sciadv.adh5435
|View full text |Cite
|
Sign up to set email alerts
|

Spatially offset optical coherence tomography: Leveraging multiple scattering for high-contrast imaging at depth in turbid media

Abstract: The penetration depth of optical coherence tomography (OCT) reaches well beyond conventional microscopy; however, signal reduction with depth leads to rapid degradation of the signal below the noise level. The pursuit of imaging at depth has been largely approached by extinguishing multiple scattering. However, in OCT, multiple scattering substantially contributes to image formation at depth. Here, we investigate the role of multiple scattering in OCT image contrast and postulate that, in OCT, multiple scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This limits the information obtained from imaging to the first couple of millimeters of tissue [ 33 ]. Excitingly, imaging depth may be increased using new approaches that illuminate the sample and subsequently collect the backscattered light from a separate path [ 37 ].…”
Section: Morphology-based Imagingmentioning
confidence: 99%
“…This limits the information obtained from imaging to the first couple of millimeters of tissue [ 33 ]. Excitingly, imaging depth may be increased using new approaches that illuminate the sample and subsequently collect the backscattered light from a separate path [ 37 ].…”
Section: Morphology-based Imagingmentioning
confidence: 99%
“…Therefore, separate evaluation of ballistically reflected photons and multiply scattered photons can offer insights into the anatomic origins of outer retinal OCT. Spatially offset OCT (SO-OCT) has been introduced to explore the impact of multiply scattered photons individually in OCT imaging. Results have demonstrated that selectively collecting multiply scattering signals can lead to significantly enhanced contrast at greater depths [22]. While this method relies on the intensity properties of the recorded signal and utilizes complex hardware to generate the spatial offset, it is worth noting that light also exhibits intrinsic polarization properties, which denote the geometric orientation of the probing light [23].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation arises because conventional OCT detects only single scattered photons, which restricts its ability to measure CBF noninvasively, although recent advancements in OCT that utilize multiple scattering have been shown to enhance image contrast. 15 On the other hand, DWS employs a separate source-detector configuration to capture multiple scattered photons, offering the advantage of a higher penetration depth of 1 to 3 cm. However, the accuracy of DWS is contingent on the tissue's optical properties like reduced scattering coefficient μ s ′ and the absorption coefficient μ a , which can vary across different tissues and patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, OCT determines absolute blood flow using the Doppler effect but is limited by a low penetration depth of 1 to 3 mm. This limitation arises because conventional OCT detects only single scattered photons, which restricts its ability to measure CBF noninvasively, although recent advancements in OCT that utilize multiple scattering have been shown to enhance image contrast . On the other hand, DWS employs a separate source-detector configuration to capture multiple scattered photons, offering the advantage of a higher penetration depth of 1 to 3 cm.…”
Section: Introductionmentioning
confidence: 99%